2009
DOI: 10.1017/s1751731109004625
|View full text |Cite
|
Sign up to set email alerts
|

Responses of hepatic blood flows to changes in intake in sheep: a meta-analysis

Abstract: This work set out to establish the response equations for hepatic blood flows in sheep and the contribution of hepatic arterial flow to hepatic venous blood flow due to changes in intake levels at constant diet composition. The FLORA (FLuxes across Organs and tissues in Ruminant Animals) database was used, and meta-analysis performed. The meta-analysis involved selection of published papers, identification of studies, description and coding of the selected dataset and statistical analysis using a covariance mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 27 publications
6
14
3
Order By: Relevance
“…In agreement with studies where the PDV and ST energetic metabolism in fasted, undernourished and fed animals were compared (Kelly et al., ; Ortigues and Durand, ), or were data compiled from literature were analysed (Bermingham et al., ; Vernet et al., ), a positive response in oxygen consumption by PDV and total ST of sheep at increased forage intake was observed in the present study. Moreover, the variability in oxygen consumption by PDV, liver and total ST was directly related to the variability in blood flow rather than to differences in artery‐venous concentrations of oxygen, which is in agreement with previous findings (Kelly et al., ; Ortigues and Durand, ; Lindsay and Reynolds, ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In agreement with studies where the PDV and ST energetic metabolism in fasted, undernourished and fed animals were compared (Kelly et al., ; Ortigues and Durand, ), or were data compiled from literature were analysed (Bermingham et al., ; Vernet et al., ), a positive response in oxygen consumption by PDV and total ST of sheep at increased forage intake was observed in the present study. Moreover, the variability in oxygen consumption by PDV, liver and total ST was directly related to the variability in blood flow rather than to differences in artery‐venous concentrations of oxygen, which is in agreement with previous findings (Kelly et al., ; Ortigues and Durand, ; Lindsay and Reynolds, ).…”
Section: Discussionsupporting
confidence: 91%
“…The average values of portal and hepatic venous, and hepatic arterial blood flow, as well as of PDV, total ST and liver oxygen consumption obtained in the present study were within the range of values reported in literature for sheep (Bermingham et al., ; Vernet et al., ). Hepatic acetylation of PAH has been reported in sheep (Katz and Bergman, ) resulting in underestimation of PAH concentration in hepatic vein blood and, consequently, in overestimation of the hepatic artery and hepatic vein blood flows if no deacetylation step was introduced in the analysis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the recalculations of the net hepatic and splanchnic fluxes using a hepatic arterial blood flow contribution of 0.10 (instead of 0.053) led to no modification of the net hepatic Phe fluxes in the C, LN and LE diets and an alteration of ,0.04 in the net splanchnic Phe fluxes in the same three diets (data not shown). In addition, an absence of significant changes in the contribution of the hepatic arterial to total venous blood flow with intake has been previously shown (Vernet et al, 2005). Lastly, results from Ortigues-Marty et al (1994) and Huntington (1982) have shown that the portal and hepatic blood flows can be measured with a relative standard deviation (r.s.d.)…”
Section: Discussionmentioning
confidence: 87%